Factors Influencing Information Source Utilization among Maize Farmers in Edo State, Nigeria - Okoedo-Okojie, D. U. (Current Approaches in Science and Technology Research Vol. 1, 2021)
This study identified determinants of constraints to information sources utilization among maize farmers in Edo state, Nigeria. In agriculture, the role of information cannot be over emphasized in enhancing the agricultural development. Information is crucial for increasing agricultural production and improving marketing & distribution strategies .Data were collected from 150 randomly selected maize farmers with the aid of structured questionnaire validated by expert judgment, and analyzed using frequency, percentage, mean and Chi-square for hypothesis testing. Results showed that majority (66.0%) (59.3%) (53.3%) and (50.7%) of the respondents had farm size of < 1 hectare, were married and males and household heads, respectively. Most preferred information sources were radio (M = 2.69) fellow farmer (M = 2.60), posters and bill board (M = 2.59), and books and leaflets (M = 2.58). Most serious constraints faced in the use of information sources were poor radio and television signals (M = 3.42), inadequate rural electrification and constant power interruption (M = 3.23), agriculture information and radio aired at odd hours (M = 3.15), lack of time to listen to agriculture information (M = 3.10), agriculture information is not broadcast on radio and television in my area (M = 2.99). There was a significant relationship between access to credit (R2 = 7.416), farm ownership (R2 = 12.497) sex (X2 = 13.759) of respondents and constraints encountered in information sources utilization at 0.05 level of significance. It was recommended that the Ministry of Agriculture should study time for broadcasting agriculture information in understandable language to attract maize farmers to listen, Radio and television signals needs to reach rural areas to improve audience level of farmers for increased proven technologies information utilization.